Differences Of Reciprocal Teaching And Problem Solving Learning On Mathematics Reasoning Ability And Mathematic Representation - Piliang, Maysarah (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
This study aims to determine the differences in learning Reciprocal Teaching and Problem Solving on the ability to reason and mathematical representation in Mathematics Statistics Class XI MAS Al-Washliyah Tembung 2018/2019 Academic Year. This research is a quantitative research, which is a quasi-experimental research type. The population of all students in class XI totaling 60 students, experiment 1 sampled 30 students and experiment 2 also 30 students. The test instrument used is a mathematical reasoning ability test and a representation ability test, each of which consists of 5 questions in the form of descriptions. The results of the F test analysis contained in the summary of ANOVA results, obtained the value of F count = 0.439 and F table at the level (α = 0.05) = 3.923. The findings of the population Fcount < Ftable, then there are differences in reasoning abilities and mathematical representation abilities between students who are taught by learning Reciprocal Teaching and learning Problem Solving in Statistics. The mathematical representation ability of students who are taught by learning Reciprocal Teaching is better than students who are taught by learning problem solving on circle material in class XI MAS Al Washliyah Tembung.